The Effect Of Using Medial Arch Support On Dynamic Balance - Agus Setyo Nugroho; Prasetyo Catur Utomo (Poltekkes Kemenkes Surakarta, 2022)
Background: Pes planus is a clinical orthopedic condition in which the medial longitudinal arch is not visible from birth and the area is covered with fatty tissue, by using medial arch support it is hope that it can encourage the formation of the medial longitudinal arch and position the sole of the foot in the correct potition The arch normally forms from the first 5 years with an age range of 2-6 years. The critical period for arch formation is 6 years of age (Campbell, 2012). In the early school years, 28% - 35% of children have pes planus deformities, 80% of whom are categorized as